Length scale dependence in elastomers – comparison of indentation experiments with numerical simulations. (19th August 2016) - Garg, Nitin; Han, Chung-Souk; Alisafaei, Farid
Abstract: Probing depth dependent deformation at nano- and micrometer length scales has been observed in indentation experiments of polymers. Unlike in metals, where size effects are observed in plastic deformation and are attributed to geometrically necessary dislocations, the origin of size dependence in polymers is not well understood. As classical continuum theories are unable to describe such phenomena, higher order gradient theories have been developed to capture such size dependent deformation behavior. The present study adopts the penalty finite element approach for a couple stress elasticity theory under axisymmetric conditions to numerically simulate and analyze the probing depth dependent deformation. Polydimethylsiloxane (PDMS) and natural rubber have been used as model materials to analyze the depth dependent deformation at different probing depths. Simulations were performed on PDMS using spherical indenter tips of different radii to show the influence of strain/rotation gradients on elastic modulus. To capture the experimentally observed increase in hardness with decreasing probing depth, simulations applying a conical indenter tip were performed and compared with experimental data. Graphical abstract: Highlights: Indentation size effects in elastomers are analyzed with a couple stress theory implemented in a finite element (FE) approach. The FE simulations were performed for both conical indenter tips at various indentation depths and spherical indenter tips of various tip radii. Good agreement has been found in experiments and simulations corroborating the notion of higher gradient dependent deformation in elastomers.